Do princípio da precaução à ética da responsabilidade: em busca dos pressupostos para a construção do estado democrático de direito ambiental - Nascimento, Ademariza Bahls do (Universidade do Vale do Rio dos Sinos, 2012)
It is undeniable that today's society is experiencing an environment crisis, due to the depletion of environmental assets that compromises the quality of human life, due to technological and industrial advances. A balanced and healthy environment is everyone's right and constitutionally recognized. The modern State has as an obligation the environmental protection in order to preserve the environment for present and future generations. It is essential the balance between economic development and environmental preservation seeking a sustainable development. Therefore, the current Democratic State of Law needs to move toward building a Democratic State of "Environmental" Law. It highlights the contribution of structural constitutional principles of a Democratic State of Law in this task. Among them: the principle of the Democratic State and of the Law, Republican Principle and the Principle of Human Dignity. The search for sustainability should be one of the objectives of the State of Environmental Law. It is important to verify the contribution of an expansion of the qualitative concept for also a quantitative concept of the sustainability, by creating a new indicator, the Index for Sustainable Human Development. Stand out as structuring principles of the Democratic State of Environmental Law the principles of: precaution, prevention, responsibility, cooperation and the polluter pays. And yet, the contribution of the application of the Proactionary Principle, a review of the precautionary principle, which advocates taking proactive measures in protecting the environment. It analyzes judicial decisions in order to verify the application of these principles in lawsuits related to environmental protection. The construction of a Democratic State of Environmental Law finds limitations and possibilities. Therefore, using the contribution of philosophy to the proposal for a new ethic of responsibility, prudence and care for the environmental future, through a review of the phronesis of Aristotle and the ethics of responsibility by Hans Jonas, as a possibility to implement the new State model proposed.
Keywords: Estado de direito ambiental; Princípios; Crise; Sustentabilidade; Ética; State of environmental law; Principles; Crisis; Sustainability; Ethics; ACCNPQ::Ciências Sociais Aplicadas::Direito